Santé publique et assistance en milieu rural à travers les fonds d’archives des petites communes du Val-d’Oise (1800-1945) - Roselyne Chapeau; Cécile Ribet (In Situ)
During the nineteenth century and the first half of the twentieth century, responsibility for the health of the population was increasingly taken on board by public authorities, under the pressure of hygienists and their preoccupations, which were both sanitary and social. Town dwellers were the first to benefit from this attention, whilst country dwellers, in order to avoid disease, in order to be taken care of and even, for the poorest, in order simply to survive, had to rely more heavily on local initiatives and private charity. Legislation which was gradually enacted, in particular under the Third Republic, was often only a codification and reinforcement of practices already to be seen in the 1850s. The local archives of communes with populations below 2,000 inhabitants (which according to French heritage law have to be deposited at the departmental archive centre) can sometimes shed light on the initiatives of these communes where hygiene and salubrity are concerned, even prior to the municipal law of 1884 which gave the mayor responsibility for these questions. Historians thus have at their disposal a corpus of documents which deal with epidemics and their prevention, concerning both animals and human beings. These communal archives also contain rich research material on the question of public welfare. Files on people sent to hospital are few and far between, but files on public help given to the poor and the elderly are regularly present.